(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
This article is devoted to the legal analysis of the legal consequences of unjustified interference with journalistic activities. The article shows that until this period, the law regulating social relations related to unjustified interference in journalistic activities has not been adopted . It is justified that this social relationship cannot be regulated through the analogy of law and law.